2004
DOI: 10.1017/s0022112003007031
|View full text |Cite
|
Sign up to set email alerts
|

Scattering of incident disturbances by an annular cascade in a swirling flow

Abstract: Analytical and numerical analyses are developed for the interaction and scattering of incident acoustic and vortical disturbances by an unloaded annular cascade in a swirling flow. The mathematical formulation uses the Euler equations linearized about an axial and swirling mean flow. The incident disturbances are decomposed into nearly sonic and nearly convected disturbances using the results of a normal-mode analysis, namely the unsteady pressure is predominantly associated with the former. Exact non-reflecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
53
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(55 citation statements)
references
References 21 publications
2
53
0
Order By: Relevance
“…The emergence is around 3, 8, and 5 dB in the range of Strouhal numbers [1.75,29] for the configurations T1-C1, T2-C1, and T1-C2, respectively, and around 10 dB in [0. 9,29] for T2-C2, as shown in Fig. 7 for U x d 80 m=s.…”
Section: Acoustic Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…The emergence is around 3, 8, and 5 dB in the range of Strouhal numbers [1.75,29] for the configurations T1-C1, T2-C1, and T1-C2, respectively, and around 10 dB in [0. 9,29] for T2-C2, as shown in Fig. 7 for U x d 80 m=s.…”
Section: Acoustic Resultsmentioning
confidence: 94%
“…It is so when using an acoustic analogy in rectilinear configuration (Green's function for rectilinear configuration) with the present model of blade loading. It would be so as well with a fully three-dimensional annular-cascade response function, accounting for the real geometry and applying the acoustic analogy in an annular duct, in the same way as with the three-dimensional seminumerical models of Namba [27] or Schulten [28], or with a code solving the three-dimensional linearized Euler equations [29]. Hanson's approximation does not exhibit any singularity, since its direct-radiation formulation is equivalent to an acoustic analogy in a rectilinear configuration and since the present unsteady blade loading is suited to rectilinear cascades.…”
Section: Comparison Of Measured and Predicted Resultsmentioning
confidence: 99%
“…Several studies [1,2,3] have shown that the swirl modifies the number of acoustic modes in the duct, their radial profile and alters the incident disturbance in rotor-stator interaction. The present study is a part of an ongoing work dedicated to account for the swirling mean flow effect on rotor-stator fan noise prediction.…”
Section: Introductionmentioning
confidence: 99%
“…The incident turbulent flow consists in a uniform base flow and an isotropic, locally homogeneous fluctuating velocity field. The model has also been extended to include nonuniform base flows [8] and different energy spectra [9]. The fluctuating components of the inflow velocity field are described as a sum of Fourier modes and the propagation model is solved in the frequency domain.…”
Section: Introductionmentioning
confidence: 99%